THE ANALYSIS OF CODE SWITCHING AND CODE MIXING PHENOMENON IN ENGLISH FACEBOOK GROUP OF YOUTH COMMUNITY - Juvrianto Chrissunday Jakob (English Education Department at FKIP Nommensen University, 2020)
The phenomenon of code switching and code mixing has appeared in our daily life as an event or a trend around us. Facebook as a social media has become of code switching and code mixing phenomenon. This study aimed to analyze and to compare the kind of code switching and code mixing in Facebook group of English Youth Community. The analyzing process of code switching and code mixing in English Youth Community was taken from some comments of the members in English Youth Community where the researcher took screenshot of the members’ comments on Facebook group then analyzed the code switching and code mixing phenomenon in the comments of the members. The resarch subjects of this study are the members of English Youth Community on Facebook group. The method of this study was descriptive qualitative since the researcher intended to obtain the conversations among the members of English Youth Community on Facebook. The result of this study showed that intra essential code switching is the most widely used in some comments in English Youth Community than intra essential code switching and extra essential code switching. Code switching and code mixing phenomenon are done consciously by the members because of the change situation or the change of the topic in the English Youth Community group.